AN INTEGRATED DESIGN FOR A MUNICIPALITY BUILDING WITH ENERGY-PLUS TARGETS - Shalhoub, Mo’men; Amer, Shaima’; Abadi, Dareen (My University, 2021)
All governments seek to strengthen their relationship with their citizens. Accordingly, the governments have begun to pay attention for constructing buildings in every city to facilitate ways of dealing with citizens and knowing their needs. These buildings are called municipalities. Municipalities are governmental buildings, contain several departments for example, Building Licensure, Monitors, Human Resources, Construction, Surveying, Health, Water, Sewerage, Electricity and more. They provide many unlimited services in all aspects of life. The intended graduation project was an integrated redesign of the Nablus municipality building, to achieve human comfort for all people who might work in, visit or even see it, and got an energy-plus building. This results in benefits for human health, the surrounding environment, and the general economy. In order to achieve the set goals, a specific strategy was followed based on searching, studying, analyzing, finding out the problems, understanding them, suggesting possible solutions and then start designing the facility, taking into account the integration between all systems. The designing process contained different aspects including architectural redesign, structural, mechanical, and electrical design. Achieving human comfort will include thermal, acoustical, visual, ventilation comfort, and facilitate movement inside the building whether for municipality employees or visitors. (Taking into consideration the probability of the presence of people with special needs) The above process was done by starting with collecting information by conducting a literature review and a questionnaire survey, these steps were followed by making site analysis. Based on the above, the architectural redesign process has been being, the environmental performance of the 3D model will be analyzed and evaluated. after that, the mechanical distribution including water, HVAC and sewerage systems, also the electrical distribution including power systems and control panel was designed in an integrated way with the architectural and the structural design. The results of the project were introduced into a report with attached tender documents, these documents will include design details, tables of quantities, and shop drawings. The final results will be shown in the final presentation.